Language Policy and Portuguese Language teaching in the school context (Research, Society and Development, 2021)
The aim of this work was to investigate the teachers' conceptions about first language teaching and its relation with Language Policies in High school in the context in a city in the North of Minas Gerais. Therefore, we chose a qualitative and interpretative exploratory research method. For data collection, interviews were conducted with four teachers from a public school and a private school of a city in the North of Minas Gerais. On this work we discuss Brazilian Portuguese language teaching representations and how this teaching occurs in the context of the investigated schools. The hypothesis that guided this work seemed to be confirmed, at least regarding the institutions investigated, since it was verified that there is a greater emphasis on language teaching focused on the grammatical tradition, establishing the Standard Language as the only correct one, putting aside other variants. As far as Language Policy is concerned, there has been a lack of consistent Language Policies that encompasses the linguistic reality of our country. The work evidenced the need for this theme to be widely disseminated in universities, undergraduate and postgraduate courses, since many teachers are not yet familiar with this subject.